2007
DOI: 10.2304/elea.2007.4.3.266
|View full text |Cite
|
Sign up to set email alerts
|

In Medias Res: Reading, Writing, and the Digital Artefact

Abstract: In information systems and end-user computer research, ‘using’ appears to encapsulate a range of activities, such as reading, writing, viewing and so on. And yet it is a grossly inadequate descriptor for any of these activities, failing to account for the fact that texts — digital or otherwise — are produced and engaged by humans for a variety of purposes, from study to recreation. The wide adoption of ‘use’ as a descriptor for engagement with hypermedia reflects the challenges inherent in understanding and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We are particularly interested in communities of learners in teacher education settings whose interactions are mediated through the use of wikis. We focus on wiki software in particular because Dobson's research (Dobson, 2007) has demonstrated that wikis are highly versatile and open spaces for facilitating collaborative writing that encourage students to interrogate established notions of authorship and authority. Dobson (2007) has noted that further examination of their merits in this regard would be beneficial.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We are particularly interested in communities of learners in teacher education settings whose interactions are mediated through the use of wikis. We focus on wiki software in particular because Dobson's research (Dobson, 2007) has demonstrated that wikis are highly versatile and open spaces for facilitating collaborative writing that encourage students to interrogate established notions of authorship and authority. Dobson (2007) has noted that further examination of their merits in this regard would be beneficial.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We focus on wiki software in particular because Dobson's research (Dobson, 2007) has demonstrated that wikis are highly versatile and open spaces for facilitating collaborative writing that encourage students to interrogate established notions of authorship and authority. Dobson (2007) has noted that further examination of their merits in this regard would be beneficial. Moreover, although there are discussions of the possibilities for wikis and other forms of social software in formal education (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, up until recently the employment of digital technologies has heavily rested on the preservation of cultural artifact and practice knowledge, through the design and development of online digital portals that host culturally significant tangible artifacts (Pramartha and Davis 2016). The approach of creating digital artifacts, a process that engages different cognitive operations and literacy systems (Dobson 2007), has been mainly applied in formal education and its pedagogical virtues are acknowledged by recent research (Gouseti et al 2020), exemplifying anthropology’s persistence to classify material culture as principally a concern of ethnology (Pfaffenberger 1988). Nevertheless, reflecting on the history of the artifact in anthropology and its political gravity in the colonial project, we might consider a forceful appropriation of its properties in the digital realm (Apostolidou forthcoming).…”
Section: Digital Artifacts and Nodesmentioning
confidence: 99%